Multiple Intelligence and Career Preference: A Basis for Senior High School Career Guidance Orientation - Parojenog, Robin C.; Parojenog, Anna-Louise Precila R.; Atup, Ma. Delilah C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to determine the multiple intelligence and career preferences of Grade XII students of Biabas Trade High School as the basis for career guidance orientation. The respondents of the study are the 179 grade 12 students from different tracks. A descriptive survey method type of research was used in conducting the research using an adapted multiple intelligence test survey, multiple intelligence checklist, and an adapted and modified inventory of occupational interest checklist from National Career Assessment Examination (NCAE). The results were analyzed using analysis of variance and Pearson r to determine the significant difference and significant correlation respectively. The results showed that there is no significant relationship between the multiple intelligence and career preferences of the students. This implies that students have different multiple intelligences without any regard to their career preference. It was observed that among the nine multiple intelligences, the Existential and the Kinesthetic strength are most dominant among the Grade 12 Senior High School students. On the other hand, students who fall under the Logical strength are the least dominant. In terms of career preferences, the careers that fall under the Interpersonal strength are most dominant. The least dominant preferred careers are the ones that belongs to the Existential strength. Based on the given result, it is recommended that it must be disseminated to all senior high school teachers, career guidance advocates, and school heads through conference, in-service trainings, or during LAC sessions to communicate the importance of developing multiple intelligence and career guidance orientation among senior high school students.